1970
DOI: 10.1111/j.1476-5381.1970.tb10353.x
|View full text |Cite
|
Sign up to set email alerts
|

Rapid histamine assays: a method and some theoretical considerations

Abstract: Summary1. An automatic method for doing assays on superfused isolated tissues has been developed using the Autoanalyser sample turntable. 2. Responses in the range used for assays are independent of the preceding responses when elicited at 1 min intervals. A longer interval was found to be necessary when using the conventional immersion method. 3. The index of precision was similar to that reported for other superfusion methods. 4. The assay method behaved as though it were assaying histamine selectively in tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1972
1972
1976
1976

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…He found that with shortening by 50% the tension developed was negligible (Figure 1). On the other hand Colquhoun & Tattersall (1970) observed no difference between the percentage of shortening and tension of the guinea-pig ileum longitudinal muscle in response to histamine. Some physiological observations have also been published.…”
Section: Introductionmentioning
confidence: 71%
“…He found that with shortening by 50% the tension developed was negligible (Figure 1). On the other hand Colquhoun & Tattersall (1970) observed no difference between the percentage of shortening and tension of the guinea-pig ileum longitudinal muscle in response to histamine. Some physiological observations have also been published.…”
Section: Introductionmentioning
confidence: 71%
“…The equipment shown diagrammatically in Fig. 1 is a development of that described by Colquhoun & Tattersall (1970) and is based on a modified EEL Auto-sampler (model 178). This has a total capacity of 48 tubes which are held on a turntable rotated by a pulse driven stepping motor.…”
mentioning
confidence: 99%